Evaluación de los parámetros del agua termal para su consumo humano y mejora de su calidad - distrito de Cachicadán, 2019 - Vera Cordova, Marianela Ivonne (2019)
At present, the urban part of the district of Cachicadán has access to several sources of surface and groundwater with a state of apparent quality, this element is ingested on many occasions without giving it any type of treatment. Therefore, the main objective is to evaluate the parameters of water for human consumption for the improvement of the quality of supply of the district of Cachicadán, by means of physicochemical and microbiological analyzes. Three monitoring points can be identified, with three repetitions for each point, the water samples are analyzed in the laboratory of the Faculty of Chemical Engineering of the National University of Trujillo. The microbiological results indicated that the total coliforms in the source, reserve and household supply of the district of Cachicadán, exceed 3 CFU / 100 mL to 12 CFU / 100 mL the LMP, while the heterotrophic bacteria are within the established state and the Average concentration of lead in water is 0.023 mg / L exceeding ECA and LMP. These results show a risk of intoxication and a serious health problem in the population of Cachicadán